Eye-specific effects of binocular rivalry in the human lateral geniculate nucleus - Haynes, John-Dylan; Deichmann, Ralf; Rees, Geraint (Nature, 2005)
Seeing double When our eyes are presented with incompatible images, our conscious perception fluctuates spontaneously between each monocular view. The nature of the resulting ‘binocular rivalry’, and how the brain resolves it, is the subject of a long-standing debate that touches on fundamental aspects of human cognition such as attention and selection. Now a neural signature characteristic for binocular rivalry has been identified, at the very earliest stages of visual processing, in the human lateral geniculate nucleus (LGN). This region of the brain contains cells that respond only to stimulation of one or other eye, and the signals in the LGN closely reflect the perceptual dominance seen during binocular rivalry. When dissimilar images are presented to the two eyes, they compete for perceptual dominance so that each image is visible in turn for a few seconds while the other is suppressed. Such binocular rivalry is associated with relative suppression of local, eye-based representations 1 , 2 , 3 , 4 that can also be modulated by high-level influences such as perceptual grouping 3 , 5 , 6 . However, it is currently unclear how early in visual processing the suppression of eye-based signals can occur. Here we use high-resolution functional magnetic resonance imaging (fMRI) in conjunction with a new binocular rivalry stimulus to show that signals recorded from the human lateral geniculate nucleus (LGN) exhibit eye-specific suppression during rivalry. Regions of the LGN that show strong eye-preference independently show strongly reduced activity during binocular rivalry when the stimulus presented in their preferred eye is perceptually suppressed. The human LGN is thus the earliest stage of visual processing that reflects eye-specific dominance and suppression.